2019
DOI: 10.1016/j.molcel.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Modification Controls Circular RNA Immunity

Abstract: Highlights d Unmodified circRNA adjuvant induces antigen-specific T and B cell responses d m 6 A RNA modification marks self circRNAs and abrogates circRNA immunity d Unmodified circRNA and K63-polyubiquitin activate RIG-I and innate immune signaling d YTHDF2 binding of m 6 A-circRNA additionally suppresses circRNA immunity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
437
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(442 citation statements)
references
References 47 publications
5
437
0
Order By: Relevance
“…additionally, activation of riG-i signalling by 5′-PPP rNa was shown to facilitate tumour responsiveness to checkpoint inhibitors 189,190 . Furthermore, in vitro synthesized circular RNAs have been proposed to activate RIG-I, and such RNA preparations induce antitumour responses in an in vivo model 191,192 . Circular rNas lack a 5′ end and whether riG-i activation is mediated directly by circular rNas or by other contaminating rNas is controversial 192,193 .…”
Section: Box 2 | Therapeutic Approaches and Synthetic Rlr Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…additionally, activation of riG-i signalling by 5′-PPP rNa was shown to facilitate tumour responsiveness to checkpoint inhibitors 189,190 . Furthermore, in vitro synthesized circular RNAs have been proposed to activate RIG-I, and such RNA preparations induce antitumour responses in an in vivo model 191,192 . Circular rNas lack a 5′ end and whether riG-i activation is mediated directly by circular rNas or by other contaminating rNas is controversial 192,193 .…”
Section: Box 2 | Therapeutic Approaches and Synthetic Rlr Agonistsmentioning
confidence: 99%
“…Furthermore, in vitro synthesized circular RNAs have been proposed to activate RIG-I, and such RNA preparations induce antitumour responses in an in vivo model 191,192 . Circular rNas lack a 5′ end and whether riG-i activation is mediated directly by circular rNas or by other contaminating rNas is controversial 192,193 . Finally, stimulation of rLrs is of therapeutic use in vaccination models, which may be related to their role in modulating immune cell functions 186,[194][195][196][197] .…”
Section: Box 2 | Therapeutic Approaches and Synthetic Rlr Agonistsmentioning
confidence: 99%
“…It is also conceivable that circRNAs set epigenetic marks on viral or host cell genes, making circRNA abundances to perform specific functions less relevant. Finally, N 6 -methyladenosine modification in circRNAs has been shown to impact innate immune responses [5658]. Thus, differential modification of circRNAs that are up-regulated or down-regulated during viral infections may systemically deliver innate sensors to uninfected bystander cells.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2017, Howard Y. Chang reported that cells can recognize intracellular circRNA (endogenous circRNA) and in vitro synthesized circRNA (exogenous circRNA) by retinoic acid-inducible gene I (RIG-I), which can activate the autoimmune pathway (40). Then, they further proved that circFOREIGEN or PEI packaging circFOREIGEN both can play a similar role to poly(I: C) in vivo, and found that cells can distinguish between endogenous circRNAs and exogenous circRNAs by identifying whether carried N6-Methyladenosine modification (m6A modifications) (41). They further concluded that exogenous circRNAs without m6A modification bind to K63-linked ubiquitin chains (K63-Ubn) and RIG-I and promote RIG-I polymerization and activation, thereby promoting the polymerization of downstream mitochondrial antiviral signal (MAVS) and inducing the dimerization activation of Interferon Regulating Factor 3 (IRF3), and ultimately inducing the expression of genes in the autoimmune pathway.…”
Section: Circrnas In Immune Regulationmentioning
confidence: 99%